The Role of Aptitude Treatment Interaction Instructional Model with Task and Forced Instructional Strategy on Student Mathematical Reasoning Ability - Serlina Serlina; Leonard Leonard (Journal of Instructional Development Research, 2019)
This research was conducted to determine the effect of aptitude treatment interaction (ATI) instructional models with task and forced instructional strategy to mathematical reasoning abilities. Mathematical reasoning ability is an ability that belongs to the goals of national education, but its achievement is still fairly low. The method used in this study is a quasi-experimental method with a poststest-only research design. Sampling in this study using purposive sampling technique. The study sample consisted of 60 students divided into two classes (30 experimental classes and 30 control classes). This research was conducted in the school of SMK Perintis 1 Depok and SMK Fajar Depok. The experimental class uses aptitude treatment interaction (ATI) learning model with task and forced learning strategies, while the control class uses conventional methods. The collected data is then analyzed using the calculation of chi-square test, fisher test and hypothesis testing. The results of the data analysis showed that the average value of students who learned using aptitude treatment interaction (ATI) learning model with task and forced learning strategies was higher than the average value of students who learned using conventional methods. Based on the results of hypothesis testing shows that there is an influence of aptitude treatment interaction (ATI) learning model with task learning strategies and forced on students' mathematical reasoning abilities.